Hubungan Tingkat Pengetahuan dan Sikap Ibu Menyusui dengan Pemberian ASI Eksklusif di Desa Donomulyo - Sari, Ellen Dwy Puspita; Alfitri, Rosyidah; Ilmiah, Widia Shofa (Fakultas Ilmu Kesehatan, 2025)
The first thousand days of life is a period of one thousand days from conception until the child is 2 years old. Exclusive breast milk have an important role in a baby's growth, especially in the first 1000 days of their life. Currently, exclusive breastfeeding in Indonesia is still low, because it is influenced by low knowledge about the benefits and importance of breastfeeding, low support from family and those closest to them, lack of education from health workers and breastfeeding counselors in the community. The aim of this research is to determine the relationship between the level of knowledge and attitudes of breastfeeding mothers towards exclusive breastfeeding. The design of this research is cross sectional with a retrospective approach. Data analysis includes Bivariate Analysis with Chi Square and Multivariate Binary Logistic Regression Analysis. The results of the study stated that the level of knowledge about exclusive breastfeeding was good (69.2%). Most breastfeeding mothers' attitudes are negative (53.8%). The majority of breastfeeding mothers did not give exclusive breastfeeding (51.9%). There is a significant relationship between the level of knowledge and attitudes of breastfeeding mothers towards exclusive breastfeeding (sig<5%), where the attitude factor has a greater influence than the level of knowledge.